Mechanism Training Management of Innovative Talents In Higher Education Under Liaoning Province - Guoqing, Liu; Howattanakul, Sutida; Pruettikul, Sataporn (วารสารวิจัยธรรมศึกษา, 2023)
The objectives of this research were: (1) to examine the composition factors of innovative talents training management in higher education under Liaoning Province; and (2) to propose the management mechanism of innovative talents training in higher education under Liaoning Province. This research was a mixed method study. The population is administrators, professors, instructors of 20 universities under Liaoning Province. They have many years of experience in innovation education and talent cultivation management. A total of 877. Krejie and Morgan (Table 1970) obtained a total of 280 samples using stratified sampling technique. There are five key information providers, namely experts and scholars in innovation education and talent cultivation management. Obtained through purposeful sampling. The tools used for data collection include semi-structured interview form, five-level questionnaire and focus group discussion form. The research was divided into three processes: research plan preparation, research procedure and research report. Statistical data used for data analysis include frequency, percentage, average, standard deviation, and combination of exploratory factor analysis and content analysis. The research results showed that: (1) there were four components of Mechanism training management of innovative talents in higher education under Liaoning Province which consisted of management of innovative education process, the internal management of innovative talent training, the innovative talent training mode in colleges and universities, and the improvement of students' innovative ability; and (2) There are 14 strategies for the management system of innovative talents cultivation in colleges and universities under Liaoning Province: there were four strategies for the management of innovative education process, three strategies for the internal management of innovative talents cultivation, three strategies for the innovative talents cultivation mode in colleges and universities, and four strategies for improving students' innovative ability. The research results were aimed at promoting and improving the development of innovative talent training management system in colleges and universities under Liaoning Province.